Detection of Potyvirus using RT-PCR and ACP-ELISA of Dioscorea species and in vitro shoot multiplication of the virus free plants - Wulandari, Dyah Retno; Ermayanti, Tri Muji (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2011)
Detection of Potyvirus using Reverse Transcription-Polymerase Chain Reaction (RT-PCR) and Antigen Coated Plate-Enzyme Linked Immunoabsorbent Assay (ACP-ELISA) for Dioscorea alata, D. hispida and D. esculenta was conducted in order to establish in vitro culture of virus-free of these species. Plants were collected from Yogyakarta, Lampung, Pasuruan, Jakarta and Bogor. Total RNA of plants grown in a greenhouse was then isolated according to Simple Direct Tube (SDT) method. Total RNA from symptomatic leaf of Yard Long Bean (Vigna unguiculata) infected with Bean Common Mosaic Potyvirus (BCMV) was used as the positive control treatment. RT-PCR assay with degenerate primers MJ1(F) and MJ2(R) was used to identify the Potyviruses infecting Dioscorea. ACP-ELISA with antibodies specific to group Potyvirus was carried out to detect Potyvirus from leaves samples. The Dioscorea virus-free species was then cultured on modified MS medium. Shoot tips or internodes were used as explants. The results showed that using both RT-PCR and ACP-ELISA, all species tested were free from virus. The growth response of explants on MS medium was varied depending on the plant species and the concentration of BAP. Â Â Keywords: Dioscorea spp., Potyvirus, RT-PCR, ACP-ELISA, in vitro shoot multiplication